Homolytic Photocleavage of the B–N Bond in N-Heterocyclic Carbene Borane Scaffolds: Towards Efficient Type I Photoinitiators - Telitel, Sofia; Blanchard, Nicolas; Graff, Bernadette; Lalevée, Jacques; Lacôte, Emmanuel (Synthesis, 2025)
A new family of Type I photoinitiators based on N-heterocyclic carbene borane is introduced. The compounds are synthesized using a previously unknown homolytic B–N cleavage reaction. Three original NHC-amino borane compounds were designed and synthesized, and their UV absorption properties were assessed. All exhibit high molar extinction coefficients and frontier orbitals on the N-atom-bearing group. Their photolysis is rapid. ESR experiments clearly support the B–N homolytic bond cleavage to both NHC-BH2• and a delocalized radical centered mostly on sulfur. Outstanding polymerization profiles of a benchmark trifunctional acrylate monomer are noted in laminate, where the final acrylate conversions reached 70% with filtered light (λ > 300 nm).
Keywords: radical reactions; photochemistry; polymerization; cleavage; N-heterocyclic carbenes; boranes